2012
DOI: 10.1038/ismej.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity of subterranean microbial communities in deep granitic groundwater supplemented with methane and H2

Abstract: It was previously concluded that opposing gradients of sulphate and methane, observations of 16S ribosomal DNA sequences displaying great similarity to those of anaerobic methane-oxidizing Archaea and a peak in sulphide concentration in groundwater from a depth of 250-350 m in Olkiluoto, Finland, indicated proper conditions for methane oxidation with sulphate. In the present research, pressure-resistant, gas-tight circulating systems were constructed to enable the investigation of attached and unattached anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 30 publications
6
62
1
Order By: Relevance
“…In a previous study, the production of at most 320 mM acetate was observed in FCCSs charged with ONK-PVA6 groundwater, and it was speculated that the acetate was produced by microorganisms using methane as the source of carbon (Pedersen 2013). Several of the SRB in ONK-PVA6 (Table 7) are known as complete acetate-oxidizing genera, i.e., Desulfobacterium (Brysch et al 1987), Desulfobacula, and Desulfotignum (Kuever et al 2001).…”
Section: Effect Of Sulphate On Srb Diversity and Activitymentioning
confidence: 96%
“…In a previous study, the production of at most 320 mM acetate was observed in FCCSs charged with ONK-PVA6 groundwater, and it was speculated that the acetate was produced by microorganisms using methane as the source of carbon (Pedersen 2013). Several of the SRB in ONK-PVA6 (Table 7) are known as complete acetate-oxidizing genera, i.e., Desulfobacterium (Brysch et al 1987), Desulfobacula, and Desulfotignum (Kuever et al 2001).…”
Section: Effect Of Sulphate On Srb Diversity and Activitymentioning
confidence: 96%
“…The influence of viruses on microbial processes has been identified as an important factor to include in model studies. In particular, they seem to have an important mitigation effect on sulphide production by SRB (Eydal, 2009;Kyle, 2008a;Pedersen, 2013) Microbial biofilms was found to significantly influence the sorption of radionuclides on glass and rock surfaces (Anderson, et al, 2006a(Anderson, et al, , 2007. In addition, it has been demonstrated that microbial iron oxidising biofilms are strong sorbents for trace elements (Anderson, et al, 2006b;Anderson and Pedersen, 2003).…”
Section: High-level Waste Repositoriesmentioning
confidence: 98%
“…Sampling procedures have been developed and thoroughly tested, as have underground facilities for model studies (Nielsen, 2006;Pedersen, 2012aPedersen, , 2013. The first important parameter to analyse in repository environments is biomass.…”
Section: High-level Waste Repositoriesmentioning
confidence: 99%
See 2 more Smart Citations